The Impact of Dependency Burden on Urban Household Health Expenditure and Its Regional Heterogeneity in China: Based on Quantile Regression Method - Xu, Xiaocang; Wang, Qingqing; Li, Chang (Frontiers in Public Health, 2022)
Background: The aging population has led to a growing medical burden. According to National Bureau of Statistics of China, the old-age dependency ratio rose from 10.7% in 2003 to 17.8% in 2019, with a growth rate of 66.36% in China. Methods: This paper tries to use Quantile regression method to discuss the influencing factors of health expenditure in urban China based on China Household Finance Survey (CHFS), especially dependency burden. Moreover, its regional heterogeneity is also compared. Results: The old-age dependency ratio, age, family size, self-rated health status, and income significantly impact the health expenditure of urban families at the national sample quantile regression; Dependency burden and other variables on urban household health expenditure have great regional heterogeneity;The correlation between the urban health expenditure and their residence is the most stable and strong in western China. Discussion: Government should to establish a healthcare system for the elderly population suitable as soon as possible; we should pay attention to the introduction of professional medical personnel and the configuration of precision medical equipment in the western region to improve the health system in the western region.